Wireless energy harvesting for portable devices using split ring resonator - Zainal ‘Abidin, Balqis Mohamed; Khalifa, Othman Omran; Elsheikh, Elsheikh Mohamed Ahmed; Hassan Abdalla Hashim, Aisha (IEEE, 2015)
Now days, wireless charging is a through-aircharging method with growing popularity and attention. Currently, majority of wireless devices depend on battery power for their functions, and these batteries must be replaced or recharged when depleted; this invariably is a major limitation for remotely located systems. In this paper, a novel collector based on metamaterial particles, in what is known as a Split Ring Resonator (SRR), to harvest electromagnetic energy is proposed and presented. In addition, a critical review on various methods of Wireless Charging Technologies emerged these days was highlighted. There are three found methods of wireless charging;RF Waves harvesting, Inductive charging and Magnetic Resonance. The proposed method is much smaller in size and more efficient than existing collectors (antennas). A feasibility study of SRRs to harvest electromagnetic energy is conducted using a Computer Simulation Technology (CST). When excited by a plane wave with an H-field normal to the structure, a voltage is measured across a surface mount resistive load inserted in the gap of a single lo op SRR. Finally, suggesting some future works of making a 9X9 SRR and loaded the SRR with rectifying circuit to increase its efficiency, applicability and reliability.